Studnia – szczególny obiekt w przestrzeni stanowiska archeologicznego. Wprowadzenie do problematyki badawczej - Piotrowska, Magdalena; Michałowski, Andrzej (Folia Praehistorica Posnaniensia, 2019)
A significant increase in the amount of materials obtained from the recent large area excavations resulted in numerous finds of wells. For years, these unique archaeological features were not treated as a separate research problem. In order to obtain the fullest research results, an increasing interdisciplinarity involving different fields of science is applied to the studies on wells nowadays. Constructions made of organic raw materials are extremely rare in the space of a typical archaeological site and they are also extremely important sources for gaining knowledge about particular settlements. Wells are accompanied by a certain range of features related to the use of water intake and located in its immediate vicinity. These discoveries allow for extremely interesting interpretations of the functional connections between individual complexes of this type. Functions of wells are an issue that is inextricably linked to the location of such complexes in the settlement’s space. Another aspect related to studies of these features is their extremely rich symbolism. Wells are special archaeological features. Their uniqueness places them among the most interesting objects studied by archaeologists.